1973
DOI: 10.1111/j.1752-7325.1973.tb00654.x
|View full text |Cite
|
Sign up to set email alerts
|

History of Fluoride, Dental Fluorosis, and Concentrations of Fluoride in Surface Layer of Enamel of Caries‐free Naval Recruits*

Abstract: This report of a study of the concentration of fluoride in the surface‐enamel of teeth, obtained by biopsies, adds considerable information for investigators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Only option is that all dental public health specialists are employed in Indian dental school as faculty, teaching the graduates. There are nearly 1100 DPH specialists in India [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only option is that all dental public health specialists are employed in Indian dental school as faculty, teaching the graduates. There are nearly 1100 DPH specialists in India [9].…”
Section: Discussionmentioning
confidence: 99%
“…Variables Evaluated: Variables were collected to assess the demographic characteristics of the participants, the reasons for choosing public health dentistry as career, the competencies and satisfaction in career and suggestions for changes required in profession Data Collection: Updated electronic mail details of all registered public health dentists were collected from the Indian Association of Public Health Dentistry head office [9]. Each participant was contacted by electronic mail and consent to participate were sought.…”
Section: Characteristics N %mentioning
confidence: 99%
“…The enamel biopsy method for determination of fluoride [Brudevold et al. 1968;M ellberg el al., 1973a;Keene et al, 1973] was employed. The right maxillary central incisor (RC) was biopsied prior to treatment and 1 week after treatment, utilizing approximately the same areas.…”
Section: Methodsmentioning
confidence: 99%
“…Each tooth was polished for approximately 30 sec with 400-mesh silicon carbide slurry. The recovered biopsy materials were analyzed using specific ion elec trodes and atomic absorption spectrophotometry [Keene et al, 1973], Statistical analysis. The statistical analysis were done by computer using the Mi das Program of the Michigan Terminal System.…”
Section: Methodsmentioning
confidence: 99%
“…Although a number of prevalence studies have shown good correlations be tween enamel fluoride and caries scores when the subjects originated from com munities with different water fluoride lev els [Keene et al, 1973;Charleton and Schamschula, 1970;DePaola et al, 1975], the correlations were poor when the sub jects were from the same community [Ge-…”
mentioning
confidence: 99%